Epidemiological review of the association between maternal metabolic syndrome and obesity and neurodevelopmental disorders in children - Žikić, Vladica; Vučić, Vesna; Veselinović, Aleksandra; Subotić, Miško; Radovanović, Marija; Ristić-Medić, Danijela (Specijalna edukacija i rehabilitacija, 2025)
Introduction. Maternal metabolic syndrome is becoming increasingly recognized as a significant factor that can affect the health and development of children. Aim. This study investigates how MetS during pregnancy can increase the risk of obesity and neurodevelopmental disorders in children. Method. By reviewing various studies and recent data, we found that high blood sugar levels, insulin resistance, and chronic inflammation during pregnancy can lead to the stated issues. Results. This review paper indicates that addressing metabolic health in pregnant women early on can greatly reduce these risks and improve long-term health outcomes for their children. Conclusion. This study emphasizes the importance of comprehensive prenatal care that focuses on metabolic health to help prevent childhood obesity and neurodevelopmental disorders.